2-(3-Methylphenyl)-1,2-benzoselenazol-3(2H)-one - Liyun Wang; Ying Xu; Zhiqiang Guo; Xuehong Wei (IUCrData, 2017)
In the title ebselen derivative, C14H11NOSe, the nine-membered benzisoselenazolyl ring system is approximately planar (r.m.s. deviation = 0.021 Å). The dihedral angle between its mean plane and that of the 3-methylphenyl ring is 5.37 (11)°. The five-membered isoselenazolyl ring is severely strained at the Se atom: Se—N = 1.889 (2) Å, Se—Car = 1.882 (3) Å and N—Se—Car = 83.30 (10)°. In the crystal, molecules are linked by C—H...O hydrogen bonds and short intermolecular Se...O contacts of 2.6917 (19) Å, forming chains along the c-axis direction. Neighbouring molecules are linked by offset π–π interactions [intercentroid distance = 3.535 (2) Å]. The chains are also linked by C—H...π interactions, forming a three-dimensional structure.